Comparison of dental flosses - an investigation of subjective preference and mechanical properties - Zhongjin Huang; Jonathan M. Broadbent; Joanne Jung Eun Choi (Medical Journals Sweden, 2023)
AbstractObjective To investigate the properties (tensile strength, roughness, abrasiveness) of different dental flosses and how these properties relate to subjective preference for floss by users.Materials and method Four flosses of differing compositions were selected (polytetrafluoroethylene (PTFE), nylon, silk, and ultra-high-molecular-weight polyethylene (UHMWPE)). Tensile strength (TS) was measured utilising a universal testing machine (total n = 40). Surface roughness (Ra) was measured on 3D reconstructed models of scanning electron microscope and abrasiveness was measured through block-on-ring tests against human enamel. Subjective preference for floss was measured by asking a sample of 16 individuals to use each floss for an 8-day period using a split-mouth design.Results The highest TS was found in UHMWPE floss (194.18[Formula: see text]24.61 MPa) while the lowest TS was found in PTFE floss (11.78[Formula: see text]0.77 MPa). Silk floss had the highest Ra (0.304[Formula: see text]0.025 µm) while PTFE floss had the lowest (0.048[Formula: see text]0.003 µm). In-vitro abrasion testing of the flosses identified no significant differences between the flosses in causing wear on tooth enamel. Subjective ratings of flosses indicated PTFE floss to be most preferred and nylon floss to be least preferred.Conclusion There was a difference in subjective preference between dental flosses composed of different materials. The PTFE floss was the overall most preferred while the nylon floss was the least preferred. There was also an association between the mechanical properties and preference for their usage, with PTFE floss being the most preferred but having the lowest surface roughness and tensile strength.Clinical Relevance This study compared a wide range of mechanical properties and subject preferences of commercially available dental floss. The results of this study can provide guidance for the recommendation of dental floss for oral hygiene routines.